Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan - Lien Nurliah; Dety Mulyanti (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2023)
This study aims to test and analyze the effect between Service Quality and Product Quality on Customer Satisfaction at PT. USSI Pinbuk Prima Software Bandung. This research uses descriptive and verifiable methods with a quantitative or numerical approach. In this study, the authors used path analysis to see how much the relationship between variables or indirectly . The results of this study show that: Service Quality has a significant positive effect on Customer Satisfaction at PT. USSI Pinbuk Prima Software Bandung the magnitude of the influence of product quality on customer satisfaction 58.5%, Product Quality has a significant positive effect on Customer Satisfaction at PT. Pinbuk Prima Software Bandung. USSI Pinbuk Prima Software Bandung by 23%. The results concluded that the model formed is included in the strong category so that in this study the variables of Service Quality and Product Quality are suitable for use to measure the structure of Customer Satisfaction.